Effect of limestone powders on compressive strength and setting time of Portland-limestone cement pastes - Thongsanitgarn P. (2014)
In this study limestone powders with different particle sizes of 5, 10 and 20 μm were used to replace a part of Portland cement in different replacement levels to produce Portland-limestone cement pastes. The percentages of limestone replacement are 0, 5, 7.5, 10, 12.5, 15 and 20% by weight. The effect of fineness and the amount of limestone powders on compressive strength and setting time are investigated. It has been established that limestone replacement causes reduce the compressive strength due to the dilution effect, but it can reduce energy consumption and CO2 emission in cement manufacturing. The fineness of limestone powder used has influence on the observed compressive strength values. From the standard consistency results, it seems that limestone has no effect on water requirement compared to Portland cement. Moreover, the increase in level of fine particles would require much water. Both initial and final setting times were decreased with an increase in the amount of limestone. Furthermore, at the same level replacement, the cement pastes using 5 μm of limestone show lower setting time than those using 10 and 20 μm, respectively. © (2012) Trans Tech Publications, Switzerland.